Evaluasi Program Pendidikan dan Pelatihan Kepemimpinan Tingkat IV Pemerintah Provinsi Nusa Tenggara Barat - Muslihin Muslihin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2016)
The purpose of this research is to explain the program implementation qualityand efectivity of the leadership training and education of forth level of the Governmentof West Nusa Tenggara Province. This research includes evaluation research program withKirkpatrick’s model (reaction, learning, behaviour, result) by using descriptive qualitativeapproach. Data collection instruments used were interview, observation guidelines, thestudy documents, and questionnaires. Data analysis using models Miles and Hubermanthrough the display of data, data reduction, and data verification. The results showed thatthe participants’ reactions to learning by training trainers in the category adequate with ascore of 76.67%, reaction training participants towards learning lectures by speakers thatare in adequate category with a score of 75.17%, according to the coach’s ability participantswith a score of 82.93 %, both in terms of system management and operational administrationby 70.62%. Participants’ reactions to the energy aspects of training and educationthat is equal to 79.03%. The effectiveness of the program in terms of the reaction of participantswas on the score of 65.52 or the adequate category and questionnaire results 91.67%of participants consider the information given during the training is less practical nature.Keywords: Program evaluation, Kirkpatrick model, leadership, training and education Tujuan penelitian ini adalah untuk menjelaskan kualitas dan efektivitas penyelenggaraanDiklat Kepemimpinan Tingkat IV pada Pemerintah Provinsi NTB. Penelitianini termasuk jenis penelitian evaluasi program dengan model Kirkpatrick (reaction, learning,beaviour, result) dengan menggunakan pendekatan kualitatif deskriptif. Instrumen pengumpulandata yang digunakan adalah pedoman wawancara, pedoman observasi, studidokumen, dan kuesioner. Analisis data mengunakan model Miles dan Huberman melaluidisplay data, reduksi data, dan verifikasi data. Hasil penelitian menunjukkan bahwa reaksipeserta diklat terhadap pembelajaran oleh widyaiswara berada pada kategori memadaidengan skor 76,67 %, reaksi peserta diklat terhadap pembelajaran ceramah oleh narasumberberada pada kategori memadai dengan skor 75,17 %, kemampuan coach menurutpeserta dengan skor 82,93 %, sistem pengelolaan baik dari segi administrasi dan operasionalsebesar 70,62 %. Reaksi peserta terhadap aspek tenaga kediklatan yaitu sebesar79,03%. Efektivitas program dari segi reaksi peserta adalah pada skor 65,52 atau padakategori memadai dan hasil kuesioner 91,67% peserta menganggap pengetahuan yang diberikanselama diklat kurang bersifat praktis.Kata kunci: Evaluasi program, model kirkpatrik, kepemimpinan, pendidikan dan pelatihan